Synthesis of ZnO nanoparticles for oilâwater interfacial tension reduction in enhanced oil recovery - Soleimani, H. (Springer Verlag, 2018)
Nanoparticles show potential use in applications associated with upstream oil and gas engineering to increase the performance of numerous methods such as wettability alteration, interfacial tension reduction, thermal conductivity and enhanced oil recovery operations. Surface tension optimization is an important parameter in enhanced oil recovery. Current work focuses on the new economical method of surface tension optimization of ZnO nanofluids for oilâwater interfacial tension reduction in enhanced oil recovery. In this paper, zinc oxide (ZnO) nanocrystallites were prepared using the chemical route and explored for enhanced oil recovery (EOR). Adsorption of ZnO nanoparticles (NPs) on calcite (111) surface was investigated using the adsorption locator module of Materials Studio software. It was found that ZnO nanoparticles show maximum adsorption energy of â 253Â kcal/mol. The adsorption of ZnO on the rock surface changes the wettability which results in capillary force reduction and consequently increasing EOR. The nanofluids have been prepared by varying the concentration of ZnO nanoparticles to find the optimum value for surface tension. The surface tension (ST) was calculated with different concentration of ZnO nanoparticles using the pendant drop method. The results show a maximum value of ST 35.57 mN/m at 0.3Â wt of ZnO NPs. It was found that the nanofluid with highest surface tension (0.3Â wt) resulted in higher recovery efficiency. The highest recovery factor of 11.82 at 0.3Â wt is due to the oil/water interfacial tension reduction and wettability alteration. Â© 2018, Springer-Verlag GmbH Germany, part of Springer Nature.